2017
DOI: 10.3906/biy-1704-11
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular presence/release of galectins from HTR-8/SVneo extravillous trophoblast cells*

Abstract: Galectins (gals) are β-galactoside binding lectins, involved in many processes at the fetomaternal interface where they can exert their roles both in and out of cells. The aim of this work was to explore the extracellular presence/release of HTR-8/SVneo extravillous trophoblast cell line galectins. To that end, conditioned medium (CM) from HTR-8/SVneo cell culture was fractionated into a high molecular mass fraction (HMF) and low molecular mass fraction (LMF) using 100 kDa cut-off concentrators. In addition, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…5e,f), thus participating in base line cell invasion. The Matrigel galectin-3 contribution to trophoblast cell invasion shown here is however hard to fully appreciate, since HTR-8/SVneo cells also release galectin-3 into the medium 36 . On the other hand, the presence of galectins in Matrigel could be seen as a factor making this matrix a better model of decidual ECM.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…5e,f), thus participating in base line cell invasion. The Matrigel galectin-3 contribution to trophoblast cell invasion shown here is however hard to fully appreciate, since HTR-8/SVneo cells also release galectin-3 into the medium 36 . On the other hand, the presence of galectins in Matrigel could be seen as a factor making this matrix a better model of decidual ECM.…”
Section: Discussionmentioning
confidence: 77%
“…Based on galectin binding specificity and potentially shared ligands, it was of interest to determine whether galectin-3 participates in processes affecting trophoblast cell migration and cell invasion. Recently, we have shown that trophoblast HTR-8/SVneo cells release galectin-1, -3 and -8 into culture medium 36 . Thus, two approaches were taken, the first one with either increased, or blocked extracellular galectin-3, and the other based on reduction of intracellular galectin-3 by targeting its mRNA.…”
Section: Discussionmentioning
confidence: 99%